Entrepreneurship integration: a paradigm-shift for sustaining architectural education innovation - Kasim, Rozilah; Gafar, Mudashir; Martin, David; Wan Yusoff, Wan Fauziah (Medwell Publications, 2016)
The prime intention of this research is to stress the potential benefit of introducing entrepreneurship teaching into the architectural education's curriculum structure. The study outlined channels of introduction and impediments that could hinder the integration. Hence, findings from the survey carried out on the current status of entrepreneurship integration in Nigerian schools of architecture provided. The study used mainly quantitative research approach through purposive sampling method. The perception of 389 students and educators of architecture program on the entrepreneurship awareness were sampled and the data collected was analysed with a Statistical Package for Social Science (SPSS). The research outcomes showed that entrepreneurship's in. tegration in. the selected Nigerian schools of architecture is still at its lowest stage. As a matter of fact, the educators' level of entrepreneurship knowledge is somewhat weak to instil entrepreneurship culture on their educatees. Orthodox teaching approach (lecture series) is still predominately used as against the innovative practical-based teaching methods required for today's competitive economic reality. Possible impediments to the entrepreneurship in. tegration and modalities on how to successfully inculcate entrepreneurship re-orientation in the young architects under training in the higher learning institutions provided. Today's reality is to position training and practice of architecture in the perspective of techno-entrepreneurialism.